2010
DOI: 10.1088/0004-637x/725/1/894
|View full text |Cite
|
Sign up to set email alerts
|

EXPANSION VELOCITY OF EJECTA IN TYCHO's SUPERNOVA REMNANT MEASURED BY DOPPLER BROADENED X-RAY LINE EMISSION

Abstract: We show that the expansion of ejecta in Tycho's supernova remnant (SNR) is consistent with a spherically symmetric shell, based on Suzaku measurements of the Doppler broadened X-ray emission lines. All the strong Kα line emission show broader widths at the center than at the rim, while the centroid energies are constant across the remnant (except for Ca). This is the pattern expected for Doppler broadening due to expansion of the SNR ejecta in a spherical shell. To determine the expansion velocities of the eje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
96
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 38 publications
16
96
1
Order By: Relevance
“…In the literature different techniques have been adopted to provide an estimate of such a distance, always returning a value ranging between 2 and 5 kpc (see Hayato et al 2010, for a review). Kinematic methods give a distance of 2.5−3 kpc (Tian & Leahy 2011).…”
Section: Modeling Tychomentioning
confidence: 99%
“…In the literature different techniques have been adopted to provide an estimate of such a distance, always returning a value ranging between 2 and 5 kpc (see Hayato et al 2010, for a review). Kinematic methods give a distance of 2.5−3 kpc (Tian & Leahy 2011).…”
Section: Modeling Tychomentioning
confidence: 99%
“…We found that Fe Kα is broadened by 101 +33 −27 eV (1-σ), for the first time from SN 1006. If this width is owing to the Doppler broadening of ejecta, as is the case of Tycho (Hayato et al 2010), the expansion velocity in the line of sight should be ∼ 3000 km s −1 . This value is consistent with that of Katsuda et al (2013), in which they measured the proper motion of the NW rim in X-ray.…”
Section: Three-dimensional Geometry Of Sn 1006mentioning
confidence: 99%
“…H i absorption studies (Tian & Leahy 2011) favor a distance on the near side of the Perseus arm (2.5 to 3 kpc). On the other hand, Hayato et al (2010) measured the shocked ejecta velocity to be about 4700 km s −1 for Si, S, and Ar. They concluded that the distance is 3 to 5 kpc on consideration of the measured proper motion.…”
Section: Introductionmentioning
confidence: 99%